Laura Orvieto et l'Histoire. Une intellectuelle florentine dans l'Histoire et pour l'Histoire - Paruolo, Elena (Ondina - Ondine, 2020)
Our article focuses on Laura Orvieto, a Jewish intellectual from Florence, Italy (1876-1953). This paper examines particularly six of her works meant for young readers, whose main themes are History and shared memories. The article first tackles the Greek stories of heroes and gods – i.e. myths (History before History), then the stories of Rome and the First World War of which the author provides a pacifying interpretation. The final part analyses Florence Nightingale’s human and pionieristic mission as she devoted part of her life to organizing army hospitals during the Crimean War.  Key words: Myth, History, stories, war, children’s literature.